CONTROLLING IN THE AUXILIARY PRODUCTION OF JSC BMZ – MANAGEMENT COMPANY OF HOLDING BMK - S. N. Astratov (Литьë и металлургия)
The advantages provided by use of controlling instruments of SAP R3 system in auxiliary production of JSC «BMZ» – management company of BMK holding are shown.